Kajian mikrobiologi ekstrak terpartisi Annona muricata Lim. Folium terhadap Propionibacterium acnes dan Staphylococcus aureus - Gemantari, Baiq Maylinda (Journal of Pharmaceutical and Sciences, 2025)
Annona muricata is a plant broadly reported to have various medicinal benefits and has been widely used around the world. The leaves are a part reported to have antimicrobial activity. This study aimed to determine the antimicrobial properties of A.muricata leaves partitioned extract against Propionibacterium acnes and Staphylococcus aureus. The partitioned extract was obtained by liquid-liquid partition of ethanolic extract using N-hexane, ethyl acetate, and ethanol. An antimicrobial study was conducted using the Kirby-Bauer method. The result showed that at the highest concentration model used, antimicrobial activity was shown in N-hexane partitioned extract and ethyl acetate partitioned extract. Those properties were known to correlate with some groups of secondary metabolites, including flavonoid, steroid, phenolic, and saponin.